THE IMPACTS OF NATIVE SPEAKER TEACHERS’ NONVERBAL COMMUNICATION IN EFL CLASSROOMS - Adhitya, Novandy; Valiansyah, Vega (English Education Department of STKIP Pasundan, 2023)
ABSTRACT This research tries to analyze nonverbal communication types employed by native speaker teachers when teaching English as a Foreign Language (EFL) classes and the effect of those nonverbal communications on students. This study employed descriptive methodology. Two native-speaking teachers in English and fifteen students comprise the study's participants. Observation and interviews were utilized to acquire data. This study found that teachers frequently employ six types of nonverbal communication. These included the application of kinesics, proxemics, ocelusics, chronemics, paravocalics, and physical appearance. The data analysis also revealed that the teachers’ nonverbal communication had both good and bad effects on the pupils. The teachers’ use of appropriate hand gestures, eye contact, and voice emotion when teaching the topic significantly helped to develop healthy teacher-student relations, particularly in motivating and appreciating students. However, eye contact can induce anxiety in students. Keywords: Nonverbal Communication, Effects of Nonverbal Communication, EFL Classroom, Native Speaker Teacher